The antioxidant effectiveness of liquorice (Glycyrrhiza glabra L.) extract administered as dietary supplementation and/or as a burger additive in rabbit meat. (December 2019) - Dal Bosco, Alessandro; Mattioli, Simona; Matics, Zsolt; Szendrő, Zsolt; Gerencsér, Zsolt; Mancinelli, Alice Cartoni; Kovács, Melinda; Cullere, Marco; Castellini, Cesare; Dalle Zotte, Antonella
Abstract: The present research studied the effect of liquorice extract (in feed and/or directly in burgers) on the shelf-life of rabbit meat. Before weaning, 28 individually caged rabbit does with their litters were divided in two dietary groups: Control, receiving a commercial diet, and Liquorice, receiving the Control diet supplemented with 6 g liquorice extract/kg (L). At 12 weeks of age, 15 fattened rabbits/treatment (one rabbit/cage) were slaughtered and their hindlegs dissected. Hindleg meat was trimmed, individually minced and divided into two parts: one of them was mixed with 0.25% (w/w) L. Storage time significantly reduced the amount of polyunsaturated fatty acids in the burger, to a different magnitude depending on the unsaturation level, experimental group and storage time. The α-tocopherol content showed higher levels during storage in the burgers from the Liquorice group. Also TBARs values showed a significant positive effect of dietary liquorice and a progressive increase at days 3 and 6 of storage. Highlights: Effect of in vivo or post-mortem liquorice extract administration on the shelf-life of rabbit burger was tested. α-tocopherol content showed higher levels during storage in the burgers from the Liquorice group. Unsaturated fatty acids (C20:5n-3 and C22:6n-3) were higher in the Liquorice groups. Storage time reduced the amount of PUFA in the burger, depending on the liquorice supply. Dietary liquorice, improved antioxidant activity and protected rabbit meat against lipid oxidation.